AI-Driven Marketing Communications and Herbal Drugs Brand Awareness Among Retirees in Southwest Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigated the effects of AI-driven marketing communication messages on herbal drugs brand awareness among retirees in Southwest Nigeria. Specifically, AI-personalized advertising, AI-optimized promotional messaging, and AI-assisted interactive engagement were tested as the explanatory variables of brand awareness among retirees in Southwest, Nigeria. Using a survey research design and Multiple Regression analysis, the three proposed hypotheses were tested.The findings revealed that AI-driven communication variables exert positive and statistically significant influence on herbal drugs brand awareness among retirees. AI-assisted interactive engagement showed the strongest predictive strength. The study concludes that AI-Driven marketing communication significantly affects brand recall and recognition among retirees. It recommends among others that herbal drug firms adopt AI-based personalization tools to improve message clarity, credibility, and audience targeting.